Sarcina ventriculi in a patient of acid peptic disease and gastric outlet obstruction: A case report on a rare microorganism - Mary Thomas, Sonia; Kutty Pothen, Lilly; Mathews, Rebecca; James, Nikita (Journal of Chitwan Medical College, 2025)
Sarcina ventriculi is a gram-positive, anaerobic, spore forming, non-motile, coccus bacteria rarely encountered in gastrointestinal biopsies. This report aims to enhance clinical awareness of this uncommon entity. We report a case of a 56-year male who presented with intermittent dyspepsia, abdominal distension and nausea. He was advised an Upper GI endoscopy which revealed incomplete gastric outlet obstruction with pyloric stenosis. A biopsy from the pylorus was taken and sent for histopathologic examination which showed S. ventriculi with characteristic tetrad and octad arrangements within the gastric lumen. Though rare, it has been increasingly reported in gastrointestinal specimens in recent times. Its pathogenic significance remains debated. However, its association with conditions like pyloric stenosis and other potentially life-threatening complications warrants clinical attention.